Las habilidades comunicativas del idioma inglés como Lengua Extranjera, a través de la inclusión de herramientas TICE en los estudiantes del tercer grado de EGB de la Unidad Educativa Emiliano Ortega Espinoza. - Robalino Davila, Laura Guadalupe (2022)
The present titling work called: The communicative skills of the English language as a Foreign Language, through the inclusion of TICE tools in the students of the third grade of EGB of the Emiliano Ortega Espinoza Educational Unit, has as its main objective to integrate the TICE to improve communication skills in learning English as a foreign language, for the development of this research, the quantitative approach methodology was used with a correlational descriptive scope, which will require an orientation of the entire investigation. Regarding the techniques used, the questionnaire was shown to obtain indexes of the main problems regarding the use of these tools for the teaching-learning processes, focusing on communication skills. Likewise, the LORI instrument (Learning Object Review Instrument) was modified, using the new adaptation designed by the Teaching Collective (Conecta 13) under a Creative Commons license, it is a tool created to evaluate the quality of educational resources. Among the results of this research, part of the analysis, selection and validation of TICE tools to design and integrate activities in relation to the communication skills of listening and speaking, taking as reference the planning elements established by the Ministry of Education in the subject of English. Being able to conclude that among the six tools that were analyzed, two were incorrectly validated and used for the design of learning activities that were included in the class plans.